Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Financial Distress - Sri Lestari Yuli Prastyatini; Elen Novikasari (Ekonomis: Journal of Economics and Business, 2023)
This study aims to determine the effect of profitability and company size on financial distress in cosmetics and household goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021. The method used in this study is a quantitative method with secondary data sources. The samples in this study were 6 cosmetics and household goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2021 with a total of 34 annual reports. The sampling technique used purposive sampling technique. Data analysis used multiple linear regression analysis and classical assumption test. The results showed that profitability had a positive effect on financial distress with a significant value of 0,000 < 0,05. Company size has a positive effect on financial distress with a significant value of 0,001 < 0,05.